“A DEVOURER THERI OWN KIND”. VIOLENCE, JUSTICE AND POPULAR CULTURE IN SANTA ROSA DE LOS ANDES: THE FORMS OF AUTHORITY TO EYES OD LABORER THE JOB KILLER, CHILE 1805 - Moreno Bazaes, Daniel (Revista de Historia Social y de las Mentalidades, 2024)
Through the micro-historical analysis of judicial  proceedings by the authorities of the village  of Santa Rosa de Los Andes and intervened by  the Royal Audience of Santiago against Juan  Francisco Varas, of Hacienda de Llay-Llay,  responsible for at least six murders and many  others crimes that undermined the local order  and civil government, is intended to realize the  intrinsic social organization in the Aconcagua  Valley at end of the  XVIII century and during  the early  XIX century. So that through the  observation of the tensions generated by the  indiscriminate use of violence, disrespect and  disobedience to authority, is intended to show  one of the most violent faces presented the  processes of ‘campesinización’ in Chile during  the colonial period, investigating the forms  in which the contemporaries, administration  and local authorities reacted to these practices  considered unacceptable and excessive. Course it  intends to account for the mechanisms deployed  to control that kind of behavior and from there to  deepen the horizons who adopted it and authority  against a popular culture that was set apart from  the "civility"
Keywords: Violence; Justice; Authority; Popular culture